Zwei unbeschriebene Cicindeliden aus der Sammlung Walther Horn. - Mandl, Karl Ferdinand jun. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
There are described as new and compared with their next relationship two species of tiger-beetles from Walther Horn’s collection: Cicindela pseudoplebeja and Megacephala (Tetracha) biimpressicollis. Nomenclatural Acts pseudoplebeja Mandl, 1960 (Cicindela), spec. n. biimpressicollis Mandl, 1960 (Megacephala Tetracha), spec. n.